Integration of logistics systems And the role of sidewalks in the port of Lattakia - بدر خضره جلال; عدنان اوسطه يوسف (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This research focuses on ways to address For the transportation and logistical challenges facing the Port of Lattakia, where logistics systems are considered a basic pillar For production in the work of the port of Lattakia , including the squares, and Stores, and the sidewalks: Which is a link between the sea and land. The aim of this research knowing the sidewalks assigned to transport goods Containers, and any custom sidewalks to transport excess goods, what are the Berth integrated in the transportation of both container and hyper cargo, And any sidewalks that are totally outside the investment, by knowing the quantity of cargo handled on each berth during the study period from year 2007-2017. And The most important results that arrived search by: The necessity increase numbers The sidewalks assigned to transport goods of the Containers, by merging some the sidewalks assigned to transport excessive cargo and make them sidewalks to transport container cargo, or exploiting the sidewalks non- Finally invested and by expanding the draft in the old basin and make the sidewalks in dedicated to transport container cargo .